Poverty, Tobacco, and Health: An Indian Scenario - Majra, JP; Gur, A (Journal of Health, Population and Nutrition, 2009)
Poverty and health have a two-way relationship. Poverty increases the vulnerability of people to disease, and sickness affects their income leading to poverty. Tobacco has been identified as a major avoidable cause of illness and premature death. In India, more than half of men and one-tenth of women use one or more forms of tobacco. Tobacco-use shows a clear and continual increase with decreasing wealth quintiles. Poor smokers, who are at a greater risk of illness, are also at a greater risk of not being treated or of falling into greater poverty if they seek treatment. Poor people spend money on tobacco that could be spent on food, shelter, education, and healthcare. These decisions can entrench families in an ongoing cycle of poverty and ill-health. The direct and indirect costs of tobacco-use are immense for national economy. This has positioned control of tobacco relevant in India's per suite to achieve the goals of poverty eradication and health for all. Key words: Health; Poverty; Tobacco-use; India doi: 10.3329/jhpn.v27i3.3373 J Health Popul Nutr 2009 Jun;27(3):316-318